ANALYSIS OF CONSUMER DECISION MAKING BEFORE AND AFTER WORD OF MOUTH PROMOTION IN MANADO (CASE STUDY OF GOJEK SERVICES) - Angela, Beybs .; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Transportation takes a crucial part to support human being activity is needed to help the people to do the various activities, supported by an increasingly widespread Internet. In this era, the users of transportation services expect a convenient, safe and affordable services, therefore the people of Indonesia is now in an uproar with the service-based online services in this application service online driver. In this case the Service Company can be seen the reputation of the use of its brand by providing the best experience to be a natural consumer, so that the company and others could know the standard services of a company through word of mouth promotion. Research objectives are to identify Consumer Decision Making Before and After Word Of Mouth of Go-Jek Services. This research is using in-depth interview and observation as the primary data while some journals, textbooks and some related literature are used as the secondary data. The results, there is a significant difference between before and after word of mouth promotion on consumer decision making. This can be concluded that company should care word of mouth promotion on consumer decision making based on consumer trust and consumer satisfaction.Keywords: marketing, consumer decision making, marketing communication, word of mouth.Â